Model Pemberdayaan Masyarakat Melalui Padat Karya Tunai dalam Pembangunan Desa di Kecamatan Banjar Kota Banjar - Amri Yahya; Ferey Herman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to obtain an overview of the community empowerment model through cash-intensive work policies in village development. This study uses a descriptive method with a qualitative approach. The informants in this study were 12 people consisting of 4 Village Government members, 4 BPD members, and 4 community elements. In this study, the method used was a descriptive method or descriptive survey. The researcher used research procedures, namely: (1) orientation stage, (2) exploration stage, and (3) member check stage. The researcher used data processing and analysis techniques in a qualitative approach, namely: data review, data reduction, compilation of units and categories, checking the validity of data, and data interpretation. The results of the study indicate that: 1) Community empowerment in Banjar District Village, Banjar City is carried out by involving the community and village community institutions from development planning, development implementation and evaluation of development results; 2) Villages in Banjar District, Banjar City do not implement the cash-intensive work policy which is one of the priorities for the use of village funds in accordance with the provisions of laws and regulations, because the benefits and impacts are not as expected; 3) The objectives of village development through the cash-intensive work policy cannot be achieved.